Critical pedagogy and alterative - Ortega Valencia, Piedad (Universidad Pedagógica y Tecnológica de Colombia, 2010)
It presents a phenomenological approximation to this epoch existence’s ways, by recreating them from the critical pedagogy perspective, which assumes the pedagogic action as an alterative relationship, a relation with the other one, an ethical relation based upon justice, responsibility and hospitability. There is an intention to cartography this epoch starting from the question: “In what world are we educating? There by it proposes the construction of an alterative pedagogy, which allows us to live in the political context of our daily existence with others, male and female, in a construction of a we.